A new record from East Malaysia Sphaerolaimus macrocirculus (Nematoda) - Mohd Rosli Norliana, Mohd Long Shabdin, Cheng Ann Chen, (N/A, 2013)
A new record from East Malaysia Sphaerolaimus macrocirculus (Nematoda) by Mohd Rosli Norliana, Mohd Long Shabdin, Cheng Ann Chen,